2010
DOI: 10.3989/revmetalm.0949
|View full text |Cite
|
Sign up to set email alerts
|

Estudio del mecanismo de eliminación demagnesio de aleaciones Al-Si en estado líquido mediante inyección de minerales base sílice

Abstract: ResumenSe empleó el método de inyección sumergida de polvos por medio de un gas de arrastre inerte (Ar) con el fin de eliminar el magnesio de la aleación Al-Si A380 a 750°C. Los polvos inyectados al baño de metal fundido fueron zeolita mineral, arena sílice y mezclas de ambas. Las variables de respuesta medidas fueron el contenido de magnesio en el baño metálico respecto al tiempo de inyección y las mermas de metal al final de cada experimento. En el análisis de resultados, la mezcla sílice:zeolita 66:34 % e.p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…It should be noted that the initial content of Mg in this research work is considerably high (1.6 wt-% Mg) with regard to that in other reports in the literature [4,10] that starts from 1 wt-% of Mg using enriched zeolites with different percentages of SiO 2 as bulk. Likewise, removal times over 60 min in order to reach 0.1 wt-% of Mg in the alloy are as shown by Muñoz-Arroyo et al [11]. This means that the Mg removal method using nanoparticles improves the efficiency of the process and decreases the removal time.…”
Section: Magnesium Removal By Injection Of Zeolite Without and With 2(mentioning
confidence: 62%
See 1 more Smart Citation
“…It should be noted that the initial content of Mg in this research work is considerably high (1.6 wt-% Mg) with regard to that in other reports in the literature [4,10] that starts from 1 wt-% of Mg using enriched zeolites with different percentages of SiO 2 as bulk. Likewise, removal times over 60 min in order to reach 0.1 wt-% of Mg in the alloy are as shown by Muñoz-Arroyo et al [11]. This means that the Mg removal method using nanoparticles improves the efficiency of the process and decreases the removal time.…”
Section: Magnesium Removal By Injection Of Zeolite Without and With 2(mentioning
confidence: 62%
“…Additionally, the kinetics of the Mg removal using silica is relatively slow [10]. However, in recent studies Muñoz et al [8,11] have demonstrated the feasibility of Mg removal from aluminum molten alloys by injecting zeolite (containing more than 50 wt-% of SiO 2 ) and silica using an inert carrier gas. On the other hand, nanotechnology has been applied in foundry processes to improve mechanical properties of some materials according to studies in Al alloy treatment with nano-SiC powders in order to improve toughness [12].…”
Section: Introductionmentioning
confidence: 99%
“…The use of Cl 2(g) flow, electrolysis and reactive powders are the main alternatives to decrease Mg concentrations in Al baths. 2,6,7) Muñoz-Arroyo et al 8) used rich silica based compounds such as Ca(Si 7 Al 2 ) 18 ·6H2O, KAlSi 3 O 8 and SiO 2 . In such cases the goal is to form MgAl 2 O 4 .…”
Section: Introductionmentioning
confidence: 99%